How Many M Forms are there in the Bacteriorhodopsin Photocycle? - Groma, G. I. (1986)
On capturing a quantum of light, the bacteriorhodopsin of Halobacterium halobium undergoes a photocycle involving different intermediates. The exact scheme of the photocycle and especially the number of M intermediates are subjects of debate. For a quantitative analysis of many effects connected with the photocycle, e.g. the effect of the membrane potential on the kinetics of M decay (Groma et al., 1984. Biophys. J. 45:985-992), a knowledge of the exact photocycle is needed. In the present work sophisticated measurements were made on the decay kinetics of the M forms in cell envelope vesicles, purple membrane suspension and purple membrane fragments incorporated in polyacrylamide gel. The experimental data were analyzed by fitting one, two, and three discrete exponentials. Three different real components were found in the M decay of cell envelope vesicles in 4 M NaCl. All of them exhibited a temperature-dependence obeying the Arrhenius law. Two real components were found for the purple membrane in suspension and in gel in NaCl-free medium. The third phase appeared when the gel was soaked in 4 M NaCl. As an independent means of analysis, a continuous distribution of exponentials was also fitted to the M decay kinetics in cell envelope vesicles. This calculation also resulted in three processes with distinct rates or alternatively two processes with distributed rates.